A Combined Approach of Using an SDBR and a STATCOM to Enhance the Stability of a Wind Farm - Muyeen, S.M. (2014)
This paper presents a method to enhance the stability of a grid-connected wind farm composed of a fixed-speed wind turbine generator system (WTGS) using a combination of a small series dynamic braking resistor (SDBR) and static synchronous compensator (STATCOM). The SDBR and STATCOM have active and reactive power control abilities, respectively, and a combination of these units paves the way to stabilize well the fixed-speed wind farm. In this paper, a centralized control scheme of using an SDBR and a STATCOM together is focused, which can be easily integrated with a wind farm. Different types of symmetrical and unsymmetrical faults are considered to evaluate the transient performance of the proposed control scheme, applicable to a grid-connected wind farm. The effect of a multimass drive train of a fixed-speed WTGS in fault analysis, along with its importance in determining the size of the SDBR to augment the transient stability of a wind farm, is investigated. Extensive simulation analyses are performed to determine the approximate sizes of both SDBR and STATCOM units. Dynamic analysis is performed using real wind speed data. A salient feature of this work is that the effectiveness of the proposed system to minimize the blade-shaft torsional oscillation of a fixed-speed WTGS is also analyzed. Simulation results show that a combination of a small SDBR and STATCOM is an effective means to stabilize the wind farm composed of a fixed-speed WTGS.